2023
DOI: 10.1002/ece3.9961
|View full text |Cite
|
Sign up to set email alerts
|

Reproducibility in ecology and evolution: Minimum standards for data and code

Abstract: We call for journals to commit to requiring open data be archived in a format that will be simple and clear for readers to understand and use. If applied consistently, these requirements will allow contributors to be acknowledged for their work through citation of open data, and facilitate scientific progress.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 42 publications
(27 citation statements)
references
References 28 publications
0
27
0
Order By: Relevance
“…To be fully effective, however, the data and code must be accompanied by appropriate metadata and documentation. In their call for journals to commit to improved policies around data and code, Jenkins et al (2023) describe minimum standards for archiving data and code, to ensure accessibility and useability, while Roche et al (2020) describe best practices, including adherence to ‘FAIR' (findable, accessible, interoperable, and reusable) principles (Wilkinson et al 2016), and also provide an up‐to‐date list of open‐access resources providing guidance on managing and publishing open data, including sensitive data. Indigenous data sovereignty and governance should also be a priority in many connectivity conservation projects, and for this Carroll et al (2021) provide guidance on complementing FAIR principles with CARE principles.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To be fully effective, however, the data and code must be accompanied by appropriate metadata and documentation. In their call for journals to commit to improved policies around data and code, Jenkins et al (2023) describe minimum standards for archiving data and code, to ensure accessibility and useability, while Roche et al (2020) describe best practices, including adherence to ‘FAIR' (findable, accessible, interoperable, and reusable) principles (Wilkinson et al 2016), and also provide an up‐to‐date list of open‐access resources providing guidance on managing and publishing open data, including sensitive data. Indigenous data sovereignty and governance should also be a priority in many connectivity conservation projects, and for this Carroll et al (2021) provide guidance on complementing FAIR principles with CARE principles.…”
Section: Discussionmentioning
confidence: 99%
“…An effective and comparatively low‐barrier first step is making all code and all non‐sensitive raw (unmanipulated) data openly available, ideally alongside metadata and documentation that are sufficiently detailed such that independent researchers could repeat the original analyses and achieve comparable outputs (c.f. Wilson et al 2017, Jenkins et al 2023). This step is essential for improving the transparency and reliability of connectivity models.…”
Section: Introductionmentioning
confidence: 99%
“…However, there is hope to be found here. As Culina et al (2020) have shown, journals requiring code to be shared are increasing in number yearly, and as a field, we already have improved substantially (Jenkins et al, 2023; Mislan et al, 2016). In some cases, journals have implemented far stricter (and rightly so) data and code requirements along with assigning corresponding data editors (Bolnick, 2022).…”
Section: Post‐publication: Reviewing Code After Publicationmentioning
confidence: 99%
“…Over the years, we expanded the policy to include code, programming scripts, and software, as well as detailed metadata. Earlier this year, members of the MEC and Molecular Ecology Resources ( MER ) Editorial Board (along with editors from other journals) contributed to an article in Ecology and Evolution that established minimum standards for data and code in ecology and evolution journals (Jenkins et al., 2023). While the recommendations largely reinforce what we are already doing, the article provides a description of best practices for archiving of data, metadata, programming scripts, and software, such that analyses published in a given study can be fully replicated.…”
Section: Editorial Announcementsmentioning
confidence: 99%

Editorial 2024

Rieseberg,
Warschefsky,
Burton
et al. 2023
Molecular Ecology
Self Cite